Factors Influencing the Efficient Market Hypothesis: A Stock Exchange Case Study - Regin, R.; Rajest, S. Suman; T., Shynu; Raj, Steffi (American Journal of Economics and Business Management, 2024)
The stock markets have been able to thrive due to favourable economic conditions, the push for liberalisation policies in some nations, and the trend toward globalisation of capital markets. The opportunity for international diversification and the large returns that may be on offer also entice Western equities fund managers. The question of how well these financial markets function has garnered a lot of attention as they have expanded. Time series data is represented by the data dimension, which includes information gathered in one or more variables over a specific time frame. Investment in a company's stock price and the effect of interest rates on that price are the main topics of this research. In most cases, the idea that the current interest rate is inversely related to stock prices is not disproven. Our results show that interest rates and stock prices are positively correlated, and negatively correlated. Interest rates and stock prices are completely unrelated.